THE IMPLEMENTATION OF TOTAL PHYSICAL RESPONSE (TPR) IN TEACHING SPEAKING TO YOUNG LEARNERS : A QUASI EXPERIMENTAL STUDY OF FIFTH GRADE STUDENTS AT ONE PUBLIC SCHOOL IN BANDUNG - Asri Yuniarti, - (2009)
ABSTRACT The focus of this research study was to investigate the implementation of Total Physical Response (TPR) in teaching speaking to the fifth graders of SD Tunas Harapan Bandung. Quasi-experimental design with pre-test and post-test was used in conducting the research. Therefore, two classes, each of which consists of 35 students, were selected to be samples of this research, one class as the control group and one class as the experimental group. The treatment was given in six sessions and oral speaking test was used as the research instrument on pre and post-test. Then, the scores of both groups were analyzed by using independent t-test. Based on the scores of independent t-test, experimental group students have higher speaking scores (M =7.56, SE = 1.170) than control group students (M = 7.33, SE = 1.350). Students' speaking ability in both groups was totally different as indicated by t (68) = 3.810 and sig. = .000, p < .05 with a large effect size (r = .419). In addition, the students' responses through the interview also suggested that TPR provided some advantages for students in learning speaking. In other words, the research findings confirmed that TPR was effective in improving students' speaking ability.